Obtenção de extrato enzimático da casca de abacaxi e sua utilização no preparo de hidrolisados protéicos de farinha de trigo com teor reduzido de fenilalanina e perfil peptídico nutricionalmente adequado - Raquel Linhares Bello de Araujo (2009)
Phenylketonuria (PKU) is a metabolic disease in which the untreatedindividuals can show irreversible mental retardation, and the use of wheat flour by phenylketonurics patients its not allowed. In this work, some steps were developed for obtaining wheat flour with ow-phenylalanine (Phe) content, to be introduced in phenylketonurics diet. Initially, a study was performed on the preparation and haracterization of enzymatic extracts from pineapple peel, in which their protein contents and proteolytic activities were assessed as well as the effect of pH and temperature on the proteolitic activity and stability was evaluated. After, the wheat flour proteins were enzymaticaly extracted and some parameters were tested, such as time, temperature, physical treatment of the sample, enzyme:substrate ratio (E:S) and initialconcentration of raw matter. Then, the protein extract was hydrolyzed by the action commercial enzymes and of enzymatic extracts obtained in the laboratory of the present study. Some enzymatic parameters were evaluated, such as type of enzyme, type of enzymatic association and order of enzyme action, time, temperature, pH, physical treatment of protein extract and enzyme:substrate ratio (E:S). The association of threekinds of activated carbon (AC) was used as adsorbent, varying the protein:AC ratio. The efficiency of Phe removal was evaluated by second derivative spectrophotometry measuring the Phe content in wheat flour and in its protein hydrolysates after AC treatment. To use this method was developed a procedure for single-laboratory validation. Finally, the characterization of the peptide profile of wheat flour protein hydrolysates was studied, before and after Phe removal by AC. The results showed that for the crude enzymatic extract (CE) of pineapple peel the optima values found for pH, temperature and time, corresponding to the maxima values of specific activity were 6.0, 70 ºC and 1 h 30 min. Among the three methods used for precipitation of the crude enzymatic extract, the use of ethanol was the most advantageous, leading to an extract with the highest specific activity and the optima values were: for pH 7.0; for temperature, 22 70 º C; and the time of maximum proteolytic activity was 1h 30min. The method used for protein extraction that produced the highest yield (88.53 %) was that using the initial concentration of raw matter of 1:3 (w/v), treatment with ultra-turrax, E:S of 10:100, at 40 ºC, during 2h. The parameters studied at single-laboratory validation showed fitness for the respective purpose, i.e, monitoring and controlling phenylalanine content in wheat flour. The condition that led to the smallest Phe content (503.29 mg/100g), was the one using successive association of CE (E: S 10:100, 1h 30 min) with pancreatin (E:S 4:100,3h 30 min) pH 7.0, at 50 °C, reaching 67.64% of Phe removal. Morever, the best peptide profile, from the nutritional point of view, for the two conditions, ie, before and after Phe removal, was found for the same hydrolyzate, obtained by using firstly pancreatin (E:S=4:100) for 3h 30min followed by CE (E:S =10:100) for 1h 30min, at optima conditions ofpH and temperature of each enzyme, reaching average values of 13.04 % of ditripeptides, 39.4 % of free amino acids and 12.5 % of large peptides.Key words: wheat flour, use of agroindustrial waste, protein extraction, proteinhydrolysis, Phe removal, peptide profile.